Practical prescribed-time tracking control for uncertain strict-feedback systems with guaranteed performance under unknown control directions - Zhou Yang; Yujuan Wang; Frank L. Lewis (Journal of Automation and Intelligence, 2023)
In this paper, we consider the practical prescribed-time performance guaranteed tracking control problem for a class of uncertain strict-feedback systems subject to unknown control direction. Due to the existence of unknown nonlinearities and uncertainties, it is challenging to design a controller that can ensure the stability of closed-loop system within a predetermined finite time while maintaining the specified transient performance. The underlying problem becomes further complex as the control directions are unknown. To deal with the above problems, a special translation function as well as Nussbaum type function are introduced in the prescribed performance control (PPC) framework. Finally, a PPC as well as preset finite time tracking control scheme is designed, and its effectiveness is confirmed by both theoretical analysis and numerical simulation.